UNIVERSITY NOTES. (The Accounting Review, 1926)
Abstract The article presents information about various activities taking place in several universities in the U.S. Ralph E. Badger, associate educator of finance, Brown University is leaving the department in the year 1926. A.F. Hinrichs has been appointed assistant scholar. Hinrichs has been associated with the research staff of the New York Housing Commission. Five new graduate teaching assistants have been appointed for the coming year 1927. They are scholars R.P. Doherty of Clark University, Ralph B. Tower of Boston University, Joseph Friedman of Brown, Cecil G. Garland of the University of Maine, Claude L. Stineford of Colby College. A number of changes in staff are being made in the year 1926 in University of California. Herman Helmer, lecturer in economics, W.T. McGrath, associate in economics, Rollin C. Hill, associate in economics, are leaving the department. New members of the staff are Arthur G. Coons, instructor in economics, Marion Stockwell, instructor in economics, John Clendenin, associate, Charles E. Leveson, assistant in economics and accounting.